Fabrication and mechanical properties of the biocomposites between water hyacinth fiber and paper mulberry - Prapapan Khankham (2018)
© 2017 Trans Tech Publications, Switzerland. Fabrication and mechanical properties of the bio-composites between water hyacinth natural fiber and paper mulberry have been investigated. The fabrication was performed using the hand lay-up technique. Untreated and treated water hyacinth fiber were used as reinforcements, in the ratio of 5%, 10%, 15%, and 20% by weight, with paper mulberry as a biomatrix. It has been found that paper mulberry reinforced with 15 % treated WH fiber showed maximum tensile strength and impact energy. The optical and scanning electron microscopic morphology of the obtained composites displayed a rougher surface and the decrease in the fiber diameter when treated with sodium hydroxide (NaOH). This improved the interlocking between the matrix and its reinforcement.